A COMPARATIVE STUDY OF CONSUMER PREFERENCES OF COFFEE SHOP IN MANADO (CASE STUDY: STARBUCKS AND EXCELSO COFFEE SHOP) - Thessalonica, Kereh Clarissa; Pangemanan, Sifrid S. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: The presence of coffee house modern or coffee shop has given a change of culture in Indonesia, where it is no longer only a big fan of coffee who wants to go to a coffee shop because nowadays it is not only to fulfill the functional needs but it leads to emotional needs. Consequently coffee consumption in Indonesia continues to increase, and increase consumer demand for Coffee business. The aim of this research is to analyze consumer preferences of coffee shop between Starbucks and Excelso in Manado measure by brand image, brand loyalty, price and word of mouth. This research is quantitative type of research, which uses primary data obtained through questionnaires and uses independent sample t-test as the analyticalÂ tool. The population of this research is peoples in Manado who has experience in Starbucks and Excelso coffee shop, where the sample size is taken from 100 respondents who also has experience with both stores. The result from this research found that there is no significant difference between Starbucks and Excelso coffee shop measured by brand image, brand loyalty, price and word of mouth. Starbucks and Excelso coffee shop should more considering on the factors that influence the consumer buying behavior.Â Keywords: comparative study, consumer preferences, coffee shop, starbucks and excelsoÂ